Encapsulation of anti-carbonic anhydrase IX antibody in hydrogel microspheres for tumor targeting. (1st November 2016) - Takacova, Martina; Hlouskova, Gabriela; Zatovicova, Miriam; Benej, Martin; Sedlakova, Olga; Kopacek, Juraj; Pastorek, Jaromir; Lacik, Igor; Pastorekova, Silvia
Abstract: Encapsulation is a well-established method of biomaterial protection, controlled release, and efficient delivery. Here we evaluated encapsulation of monoclonal antibody M75 directed to tumor biomarker carbonic anhydrase IX (CA IX) into alginate microbeads (SA-beads) or microcapsules made of sodium alginate, cellulose sulfate, and poly(methylene-co-guanidine) (PMCG). M75 antibody release was quantified using ELISA and its binding properties were assessed by immunodetection methods. SA-beads showed rapid M75 antibody release in the first hour, followed by steady release during the whole experiment of 7 days. In contrast, the M75 release from PMCG capsules was gradual, reaching the maximum concentration on the 7th day. The release was more efficient at pH 6.8 compared to pH 7.4. The released antibody could recognize CA IX, and target the CA IX-positive cells in 3D spheroids. In conclusion, SA-beads and PMCG microcapsules can be considered as promising antibody reservoirs for targeting of cancer cells.